10% happier : how I tamed the voice in my head, reduced stress without losing my edge, and found self-help that actually works - a true story - Harris, Dan, 1971- (Dey St., an imprint of William Morrow, 2024)
"After having a nationally televised panic attack, Dan Harris knew he had to make some changes. A lifelong nonbeliever, he found himself on a bizarre adventure involving a disgraced pastor, a mysterious self-help guru, and a gaggle of brain scientists. Eventually, Harris realized that the source of his problems was the very thing he always thought was his greatest asset : the incessant, insatiable voice in his head, which had propelled him through the ranks of a hypercompetitive business, but had also led him to make the profoundly stupid decisions that provoked his on-air freak-out. Eventually Harris stumbled upon an effective way to rein in that voice, something he always assumed to be either impossible or useless : meditation, a tool that research suggests can do everything from lower your blood pressure to essentially rewire your brain. 10% Happier takes readers on a ride from the outer reaches of neuroscience to the inner sanctum of network news to the bizarre fringes of America's spiritual scene, and leaves them with a takeaway that could actually change their lives. This fifth anniversary edition features a new preface by Harris and new guided meditations from his favorite teachers, including Joseph Goldstein and Sharon Salzberg."--Back cover.